2015
DOI: 10.1007/s10554-015-0673-3
|View full text |Cite
|
Sign up to set email alerts
|

MRI monitoring of function, perfusion and viability in microembolized moderately ischemic myocardium

Abstract: Assessment of microembolization after coronary interventions is clinically challenging, thus we longitudinally investigated microemboli effects on moderately ischemic myocardium using MRI and histopathology. Twenty-four pigs (8/group) were divided into: group I (no intervention), group II (45 min LAD occlusion) and group III (45 min LAD occlusion with microembolization). Cine, perfusion and delayed contrast enhanced MRI (DE-MRI), using 1.5T MRI, were used for assessment at 3 days and 5 weeks. Triphenyltetrazol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…In a recent proof-of-concept study, we demonstrated that mildly injured myocardium subjected to 40 min LAD occlusion then microembolization did not manifest greater susceptibility to infarction compared with solely embolized non-ischemic myocardium and 40 min LAD occlusion groups [15] (Figure 3).…”
Section: Myocardial Viabilitymentioning
confidence: 80%
See 4 more Smart Citations
“…In a recent proof-of-concept study, we demonstrated that mildly injured myocardium subjected to 40 min LAD occlusion then microembolization did not manifest greater susceptibility to infarction compared with solely embolized non-ischemic myocardium and 40 min LAD occlusion groups [15] (Figure 3).…”
Section: Myocardial Viabilitymentioning
confidence: 80%
“…In an experimental study [15], investigators found after 24 hrs PCI that plasma concentrations of CK-MB and troponin I were significantly higher after delivery of 16 mm 3 and 32 mm 3 microemboli to the LAD coronary artery compared with baseline. However, there was no significant difference at this time point in troponin I after 16 mm 3 (0.52 ± 0.28 ng/ml) and 32 mm 3 (0.68 ± 0.4 ng/ml) or CK-MB (1670 ± 370 U/L and 1060 ± 235 U/L, respectively).…”
Section: Cardiac Injury Biomarkersmentioning
confidence: 97%
See 3 more Smart Citations